[PP.21.25] COMPARISON OF VARIOUS LIPID VARIABLES IN ASSOCIATION OF TARGET ORGAN DAMAGE IN THE COMMUNITY-DWELLING ELDERLY: THE NORTHERN SHANGHAI STUDY. (September 2017) - Chi, C.; Lyu, Y.; Bai, B.; Yu, S.; Xiong, J.; Teliewubai, J.; Fan, X.; Zhou, Y.; Ji, H.; Zhang, J.; Zhang, Y.
Abstract : Objective: Low-density lipoprotein cholesterol (LDLC) is a well-established risk factor in cardiovascular diseases. However, the use of LDLC alone in cardiovascular risk assessment would ignore the influence of other lipid profiles like high-density lipoprotein cholesterol (HDLC).We therefore aimed to test the relationships between various lipid variables and target organ damage (TOD) in a community-based elderly cohort. Design and method: 1, 599 (aged 71.4 ± 6.1 years) participants in the northern Shanghai were recruited. Eight lipid variables, including total cholesterol (TC), triglycerides (TG), LDLC, HDLC, non-HDLC, TC/HDLC ratio, TG/HDLC ratio and LDLC/HDLC ratio, together with other plasma biomarkers like creatinine were measured. Pulse wave velocity (PWV) was measured by the SphygmoCor device, and ankle-brachial index (ABI) was assessed by the Omron VP-1000 device. Results: 4 conventional lipid variables (TC, TG, LDLC and HDLC) significantly correlated with most TOD indices, HDLC did not significantly correlate with PWV (P = 0.063), and TC or LDLC did not correlate with eGFR either (P >  = 0.70). All 4 "combined" lipid variables, namely non-HDLC, TC/HDLC, TG/HDLC and LCLC/HDLC, significantly correlated with TOD (P <  = 0.033). In multiple linear regression analyses, 4 combined lipid variables also significantly associated with TOD (P <  = 0.027), while none of traditional lipid variables significantly associated with all TOD indices. In multiple logistic regression analyses, only non-HDLC and TC/HDL significantly associated with TOD (P <  = 0.039), and other lipid variables did not significantly associate with TOD. Figure. No caption available. Conclusions: In an elderly community sample, non-HDLC and TC/HDLC were better associated with TOD than other lipid variables. This finding should be considered in future clinical lipid-lowing therapy.